Development of a calibration facility for optical fiber length standard - Wang, Dongliang (2009)
This report investigates two methods for measurement of optical fiber length - time of flight and frequency shifting methods. Based on comparison of their performances and costs, the time of flight method has been selected. The experiment set-up, measurement procedure and main equipments have been developed and described in detail. In order to reduce the calibration uncertainty due to resolution of oscilloscope, high order frequency modulation technique was applied to the optical signal in the calibration. The temperature effect on fiber length measurement was also investigated in the temperature range from 20 ºC to 25 ºC. Corrections were made according to temperature coefficient of the fiber under test when the calibration was done at different ambient temperatures. The calibration uncertainty components were evaluated theoretically and experimentally according to ISO/IEC Guide 98-3 standard, Guide to the Expression of Uncertainty in Measurement (GUM). The length of an optical fiber artifact was calibrated and its calibration uncertainty has been analyzed. With this calibration facility, we are able to calibrate length of optical fiber standard (~8000m) at wavelengths of 1310 nm and 1550 nm with calibration uncertainty of ±0.076 m and ±0.080 m respectively.